Sterically Shielded Heptamethine Cyanine Dyes for Bioconjugation and High Performance Near‐Infrared Fluorescence Imaging - Li, Dong‐Hao; Schreiber, Cynthia L.; Smith, Bradley D. (Angewandte Chemie, 2020)
The near‐infrared window of fluorescent heptamethine cyanine dyes greatly facilitates biological imaging because there is deep penetration of the light and negligible background fluorescence. However, dye instability, aggregation, and poor pharmacokinetics are current drawbacks that limit performance and the scope of possible applications. All these limitations are simultaneously overcome with a new molecular design strategy that produces a charge balanced and sterically shielded fluorochrome. The key design feature is a meso‐aryl group that simultaneously projects two shielding arms directly over each face of a linear heptamethine polyene. Cell and mouse imaging experiments compared a shielded heptamethine cyanine dye (and several peptide and antibody bioconjugates) to benchmark heptamethine dyes and found that the shielded systems possess an unsurpassed combination of photophysical, physiochemical, and biodistribution properties that greatly enhance bioimaging performance. It's a bird! It's a plane! Just like a superhero, an ultrastable shielded heptamethine cyanine dye uses its two strong arms to ward off self‐aggregation and non‐specific biological interactions. Yet the arms are short enough to allow dye‐labeled bioconjugates to selectively target cell receptors for high‐contrast and photon‐intense microscopy or tumor imaging in living subjects.